A randomized and blinded multicenter trial of high-dose fluconazole plus placebo versus fluconazole plus amphotericin B as therapy for candidemia and its consequences in nonneutropenic subjects - Rex, John H; Pappas, Peter G; Karchmer, Adolf W; Sobel, Jack; Edwards, John E; Hadley, Susan; Brass, Corstiaan; Vazquez, Jose A; Chapman, Stanley W; Horowitz, Harold W; Zervos, Marcus; McKinsey, David; et al. (Clinical infectious diseases, 2003)
A randomized, blinded, multicenter trial was conducted to compare fluconazole (800 mg per day) plus placebo with fluconazole plus amphotericin B (AmB) deoxycholate (0.7 mg/kg per day, with the placebo/AmB component given only for the first 5-6 days) as therapy for candidemia due to species other than Candida krusei in adults without neutropenia. A total of 219 patients met criteria for a modified intent-to-treat analysis. The groups were similar except that those who were treated with fluconazole plus placebo had a higher mean (+/- standard error) Acute Physiology and Chronic Health Evaluation II score (16.8+/-0.6 vs. 15.0+/-0.7; P=.039). Success rates on study day 30 by Kaplan-Meier time-to-failure analysis were 57% for fluconazole plus placebo and 69% for fluconazole plus AmB (P=.08). Overall success rates were 56% (60 of 107 patients) and 69% (77 of 112 patients; P=.043), respectively; the bloodstream infection failed to clear in 17% and 6% of subjects, respectively (P=.02). In nonneutropenic subjects, the combination of fluconazole plus AmB was not antagonistic compared with fluconazole alone, and the combination trended toward improved success and more-rapid clearance from the bloodstream.